Karakteristik Kimia dan Aktivitas Antioksidan Kombucha dari Tumbuhan Apu-apu (Pistia stratiotes) Selama Fermentasi - Desnilawati Hotmaria Simanjuntak; Herpandi Herpandi; Shanti Dwita Lestari (Jurnal FishtecH, 2016)
The purpose of this research was to utilize water lettuce (Pistia stratiotes) as raw material of kombucha drink and was to investigate the effects of fermentation time on chemichal characterictics and antioxidant activity of water lettuce (Pistia stratiotes) leaves kombucha. This research used randomized block design (RBD) consisted of 1 factor treatment which was fermentation time (1,4,8 and 12 days) with 3 replications. The variables observed were total sugar content, pH, total acidity, alcohol, antioxidant activity use DPPH method and sensoric analysis on appereance, colour, flavor, and taste of the find product. The result showed that fermentation time gave significant effect on chemichal analysis (total sugar content, pH, total acidity, alcohol), antioxidant activity and sensoric analysis (appereance, colour and taste), but no effect on flavor was observed.